2013
DOI: 10.1002/hpm.2198
|View full text |Cite
|
Sign up to set email alerts
|

Health workforce in the United Arab Emirates: analytic point of view

Abstract: A strong health system is impossible without health workers who are the ultimate resource. Money and medical supplies are needed, but these inputs require an efficient workforce. Challenges with respect to human resources vary greatly between and within countries, and are associated with the political, economical, cultural and societal context of a country. Moreover, the gaps in the workforce do not generally relate to doctors but to nurses and other classes of health worker who make up the bulk of health work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 24 publications
1
39
0
Order By: Relevance
“…Likewise, studies indicate that gender stereotypes persist in the health care workforce and that female health care professionals often choose specialties with lighter workloads that allow them to balance work and family . The MOHAP classifies workloads as heavy when they have an excess of unsubsidized overtime duties . De Koninck et al reported that with the strain women experience in order to balance their professional and personal lives; with the myriad responsibilities from planning pregnancies, to organizing childcare, to fostering their own career while supporting their spouse's, without sufficient support, some female doctors are drawn to specializations that allow for more time with family …”
Section: Gender Stereotypes That Results In More Male Health Care Profmentioning
confidence: 99%
See 3 more Smart Citations
“…Likewise, studies indicate that gender stereotypes persist in the health care workforce and that female health care professionals often choose specialties with lighter workloads that allow them to balance work and family . The MOHAP classifies workloads as heavy when they have an excess of unsubsidized overtime duties . De Koninck et al reported that with the strain women experience in order to balance their professional and personal lives; with the myriad responsibilities from planning pregnancies, to organizing childcare, to fostering their own career while supporting their spouse's, without sufficient support, some female doctors are drawn to specializations that allow for more time with family …”
Section: Gender Stereotypes That Results In More Male Health Care Profmentioning
confidence: 99%
“…Previously, we reported that Emirati female physicians choose to be general practitioners, and to work in peripheral health clinics to avoid working night shifts . Prevailing sociocultural norms and values of the Middle East make for strong barriers against the advancement of female physicians.…”
Section: The Concentration Female Physicians In Certain Specialtiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants included 9 men and 5 women, a gender ratio reflective of the UAE physician population. 20 During a plenary session following the world café, participants acknowledged the origins of medical professionalism in the Middle East as stemming from the Islamic Code of Medical Ethics, but highlighted the importance of developing a secular definition to facilitate the incorporation of these constructs into the multicultural setting of the UAE.…”
Section: Resultsmentioning
confidence: 99%